Hubungan Stres dengan Nilai Mean Arterial Pressure Pasien Hipertensi di Puskesmas Pati II - Desy Meliasari; Sukarmin Sukarmin; Yuli Setyaningrum (Jurnal Ners, 2025)
Hypertension is one of the serious public health problems facing the world. Systolic blood pressure ≥140 mmHg, diastolic blood pressure ≥90 mmHg above normal. Hypertension is a disease whose prevalence continues to increase globally, including Indonesia. In Indonesia, the prevalence of hypertension in the population aged ≥ 18 years reaches 32.4%. Visit data at the FKTP Pati II Health Center, recorded that hypertension sufferers were ranked 2nd in 2021 with a total of 1,226 visits diagnosed with hypertension. Stress is a natural human response that encourages us to face challenges and threats in life. Stress occurs due to stressors, stressors are triggers for stress. Mean Arterial Pressure (MAP) is the average arterial pressure during one cardiac cycle, systole, and diastole. This study aims to analyze the relationship between stress and Mean Arterial Pressure at the Pati II Health Center. The type of research used is quantitative. The population consisted of 136 hypertension patients registered at Pati II Health Center, with a sample of 45 respondents with purposive sampling. Data were collected using a questionnaire. Analyzed using the Pearson test.